Sale of goods and consumer credit - Dobson, A. P (London : Sweet & Maxwell, 1975)
The book examines the general effect of the consumer credit Act including its effect upon hire purchase transactions. It also consider common law relating to hire purchase.
Includes index.
usc 28/01/2019
Loans
Keywords: Sales; Consumer credit--Law and legislation; Conditional sales; England; Great Britain